2014
DOI: 10.3389/fmicb.2014.00414
|View full text |Cite
|
Sign up to set email alerts
|

Core functional traits of bacterial communities in the Upper Mississippi River show limited variation in response to land cover

Abstract: Taxonomic characterization of environmental microbial communities via high-throughput DNA sequencing has revealed that patterns in microbial biogeography affect community structure. However, shifts in functional diversity related to variation in taxonomic composition are poorly understood. To overcome limitations due to the prohibitive cost of high-depth metagenomic sequencing, tools to infer functional diversity based on phylogenetic distributions of functional traits have been developed. In this study we cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
56
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 46 publications
(72 reference statements)
12
56
1
1
Order By: Relevance
“…In addition, accuracy of the PI-CRUSt predictions was estimated using the Nearest Sequenced Taxon Index (NSTI) values of the two mat samples used in this study. The NSTI value validates the taxonomy-based PICRUSt-predicted KEGG functional categories of the microbial communities (Langille et al, 2013; Staley et al, 2014; Lopes et al, 2016; Kim et al, 2017). Since the output of the functional profiles generated by PICRUSt was not compatible with Tax4Fun, we have written an R script for the comparative analyses of the taxonomy-based metabolic functional predictions of the microbial communities in the two mat samples (Supplementary Materials, S1.1, S1.2, and S2).…”
Section: Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…In addition, accuracy of the PI-CRUSt predictions was estimated using the Nearest Sequenced Taxon Index (NSTI) values of the two mat samples used in this study. The NSTI value validates the taxonomy-based PICRUSt-predicted KEGG functional categories of the microbial communities (Langille et al, 2013; Staley et al, 2014; Lopes et al, 2016; Kim et al, 2017). Since the output of the functional profiles generated by PICRUSt was not compatible with Tax4Fun, we have written an R script for the comparative analyses of the taxonomy-based metabolic functional predictions of the microbial communities in the two mat samples (Supplementary Materials, S1.1, S1.2, and S2).…”
Section: Methodssupporting
confidence: 60%
“…), and surface soil samples from the Austre Lovénbreen glacier in High Arctic (mean NSTI = 0.18 ± 0.03 s.d.) (Langille et al, 2013; Staley et al, 2014; Lopes et al, 2016; Kim et al, 2017). Thus, the mean NSTI values in our study suggest that the predicted metabolic functions of the microbial communities in Lake Obersee mat samples are close to the known microbial reference genome databases, implying higher accuracy of the predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that the predominant bacterial communities in this river section were Proteobacteria, Firmicutes, and Actinobacteria, which were all once abundant in many of the freshwater lakes and reservoirs in China32 and exhibited high abundances in some other freshwater environments30333435. From these findings, we found that the bacterial communities in this section of Yangtze River exhibited a typical feature of freshwater populations.…”
Section: Discussionmentioning
confidence: 66%
“…Correction for 16S gene copy number is a built-in function of the PICRUSt functional gene prediction package (Langille et al, 2013), which has been used to investigate the functional diversity of bacterial communities in humans (David et al, 2013), salamanders (Loudon et al, 2013), and river water (Staley et al, 2014). Kembel et al (2012) showed that 16S gene copy correction of individual OTUs can affect measures of abundance for several taxa (Cyanobacteria Group II, Alteromonadales) within marine bacterial communities, as well as the structure of hierarchical clustering of communities sampled from the human microbiome.…”
Section: Discussionmentioning
confidence: 99%